Sociodemographic variables, clinical features, and treatment outcomes between two sexes in alcohol dependent patients - Pektaş, Özkan; Kalyoncu, Ayhan; Mırsal, Hasan; Beyazyürek, Mansur (Journal of Dependence, 2001)
Objective: The aim of our study is to compare clinical features, short term treatment outcomes and the other variables between two sexes in patients with alcohol dependence. Method: The participants were 36 male and 36 female inpatients were diagnosed as alcohol dependent according to DSM IV who were treated in our clinic in 1997. Thirtysix male patients confined the number of subjects included into the study. The clinical properties and sociodemographic variables are examined retrospectively from clinical records. The last conditions of patients in May 1998 were obtained from outpatient records, group session minites, and by telephone conversations. SPSS packed program was used to evaluate the obtained data. Results: The average age of subject females was 39.6 (ss=10.6) and 40.1(ss=8.9) for males. The average time of alcohol use for males were 19.6 (ss=8.6) years and 13.8 (ss=11.0) years for females. The average starting age to alcohol for males was 20,5 (SS=6.8) and 25.8 (SS=7.5)for females. These two variables showed statistically significant differences between two groups (t=2.51, P<0.01; t=3.13, P< O.OD.Dep-ression index of SCL 90 R in females and index for paranoid thoughts in male patients were significantly high. There was not meaningful differences for additional psychiatric and psychical illnesses betweeen two groups. The evaluation of patients’ last conditions (drinking alcohol, sober, unknown) showed statistically significant differences (x2= 8.3, p< 0.05). This meaningful distinction might arise from the number of unknown last conditions in male patient group because of the method of the study. Conclusion: The results of our study as the late starting age to alcohol consumption, receiving treatment early and more depressive symptoms in females, and the differences in remission rates between two groups were harmonious with the preceding studies.